Hubungan Kecerdasan Emosional dan Kecerdasan Spiritual dengan Kesepian pada Lansia di PSTW Khusnul Khotimah - Adelia Septia Nanda; Reni Zulfitri; Agrina (Jurnal SMART Keperawatan, 2025)
Introduction: Elderly undergo an aging process that causes changes across the board. Good emotional and spiritual intelligence helps elderly determine the direction and adapt to change so that they do not experience loneliness. Objective: This study aims to determine the relationship between emotional intelligence and spiritual intelligence with loneliness in elderly. Method: This research is quantitative using descriptive correlation and cross-sectional approaches. The research sample was 52 elderly people using purposive sampling technique. The instruments used in this study are Wong and Law Emotional Intelligence (WLEIS), Spiritual Intelligence Self Report Inventory (SISRI), University of California Los Angeles Loneliness scale version 3. The chi squares test statistical technique used for data analysis. Result: The majority of the elderly have high emotional intelligence 36 (69.2%), have high spiritual intelligence 33 (36.5%), and elderly did not experience loneliness 25 elderly people (48.1%). There was a significant relationship between emotional intelligence and spiritual intelligence with loneliness in elderly with a p-value of 0.00 < 0.05. Conclusion: Emotional intelligence and spiritual intelligence have a significant relationship with loneliness in the elderly. Increasing the emotional intelligence and spiritual intelligence of the elderly can reduce the loneliness felt by the elderly.